Antimicrobial susceptibility profiles of thermophilic Campylobacter species from human, pig, and chicken feces in Rwanda - Noel Gahamanyi; Arsene Musana Habimana; Jean Paul Harerimana; Josiane Mukayisenga; Salomon Ntwali; Anathali Umuhoza; Emmanuel Nsengiyumva; Emmanuel Irimaso; Jean Bosco Shimirwa; PAN, CHEOL HO; Erick Vitus Komba; Claude Mambo Muvunyi; et al. (Frontiers Media S.A., 2025)
Globally, Campylobacter jejuni and C. coli have been associated with human gastroenteritis. More importantly, there are increasing reports of Campylobacter strains that are resistant to commonly used antimicrobials. In Rwanda, the prevalence and the antimicrobial susceptibility profiles of thermophilic Campylobacter strains remain underexplored. Since human campylobacteriosis is a foodborne disease with chicken and pigs being among their major reservoirs, this study aimed to determine the prevalence and antimicrobial susceptibility profiles of thermophilic Campylobacter species from human, chicken, and pig feces in Rwanda. A total of 385, 337, and 359 human, pig and chicken feces, respectively, were investigated for the presence of Campylobacter species. Isolation was done by culture and presumptive colonies were confirmed by the Polymerase Chain Reaction (PCR). The Kirby-Bauer disc diffusion method was employed to determine the susceptibility profiles of obtained isolates against six (06) antimicrobials, namely erythromycin (ERY), ciprofloxacin (CIP), streptomycin (STR), gentamicin (GEN), tetracycline (TET), and chloramphenicol (CHL). The used antimicrobials include drugs of choice or alternative treatment for human campylobacteriosis. The overall prevalence of thermophilic Campylobacter was 7.0% (27/385) in humans, 7.1% (24/337) in pigs, and 32.0% (115/359) in chicken. C. jejuni was the predominant species in all hosts with detection frequencies of 92.6%, 66.7%, and 73.9% in humans, pigs, and poultry, respectively. Increased resistance rates to ERY (70.1？92.4%) and STR (68.2？88.0%) were observed particularly among chicken isolates. Multi-drug resistance (MDR) was observed among the isolates, with the highest rates observed in chicken isolates (88.0%). Proportions of MDR among pig (40.9%) and human (40.7%) isolates were more or less similar. These findings highlight the presence of thermophilic Campylobacter strains in humans and livestock which are resistant to commonly used antimicrobials. Based on the potential of interspecies transmission, it is recommended to adopt a One Health approach to curb antimicrobial resistance. Further genomic analysis will shed more light on the transmission and drug resistance patterns.